Analysis of Collaborative Governance in Community Empowerment of the Kampung Ramah Lingkungan Program in Garut Regency: Analisis Collaborative Governance dalam Pemberdayaan Masyarakat Program Kampung Ramah Lingkungan di Kabupaten Garut - Nurasni Syarafina Az-Zahra; Mila Karmila (Jurnal Pemerintahan dan Politik, 2026)
Purpose: To examine the implementation of collaborative governance in community empowerment through the Kampung Ramah Lingkungan Program (Kang Raling) in Garut Regency and analyze the factors influencing its success. Design/methodology/approach: Qualitative descriptive approach with a case study design. Data were collected through in-depth interviews and observations of key stakeholders. Analysis was conducted using NVivo based on Ansell and Gash's (2008) collaborative governance framework. Findings: Collaborative governance drives community empowerment through facilitative leadership of DLH, flexible institutional design, and local social capital. These mechanisms transform the community's role from program recipients to active agents in waste management. Practical Implications: This study serves as a reference for local governments in designing participatory and adaptive community-based waste management programs by strengthening facilitator roles and improving cross-sector transparency and coordination. Originality/Value: Empirically examines the relationship between collaborative governance and community empowerment in village-scale waste management, enriching Indonesian literature on cross-actor collaboration mechanisms and contextual success factors. Keywords: Cross-Actor Collaboration; Community Participation; Environmental Management. Paper type: Research paper.